LOW-TEMPERATURE MAGNETISM OF ZINC OXIDE IMPLANTED BY IONS OF 3d-METALS - M. G. Lukashevich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Monocrystalline ZnO plane have been implanted by high dose (1,5·1017 cm-2) ions of manganese, iron, cobalt, nickel with energy of 40 keV at ion current density of 4 mA/cm2 in order to modified magnetic properties. Magnetic hysteresis loops at T = 5 K, temperature dependence of magnetization at sample cooling without and in magnetic field 2 mT in the temperature range 5-300 K were investigated. The main magnetic characteristics such as coercive force, magnetization saturation and residual magnetization have been estimated. It has been also shown, that implantation of cobalt and nickel ions leads to ensemble of Langeven magnetic nanoparticles formation in zinc oxide.